2019
DOI: 10.1038/s41416-019-0661-9
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic rewiring and redox alterations in malignant pleural mesothelioma

Abstract: Malignant pleural mesothelioma (MPM) is a rare malignancy of mesothelial cells with increasing incidence, and in many cases, dismal prognosis due to its aggressiveness and lack of effective therapies. Environmental and occupational exposure to asbestos is considered the main aetiological factor for MPM. Inhaled asbestos fibres accumulate in the lungs and induce the generation of reactive oxygen species (ROS) due to the presence of iron associated with the fibrous silicates and to the activation of macrophages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 122 publications
(176 reference statements)
0
28
0
Order By: Relevance
“…In the contest of MPM, it has been demonstrated that the PI3K/AKT/mTOR pathway is frequently up-regulated probably because of the high release of reactive oxygen species (ROS) resulting from asbestos exposure. Indeed, ROS can directly lead to the inactivation of PTEN, a lipid phosphatase involved in the negative regulation of this pathway, through the oxidation of its cysteine residues [20]. Recently, loss of PTEN expression has been reported in a high percentage of human sarcomatoid MPM as compared with other subtypes [15].…”
Section: Discussionmentioning
confidence: 99%
“…In the contest of MPM, it has been demonstrated that the PI3K/AKT/mTOR pathway is frequently up-regulated probably because of the high release of reactive oxygen species (ROS) resulting from asbestos exposure. Indeed, ROS can directly lead to the inactivation of PTEN, a lipid phosphatase involved in the negative regulation of this pathway, through the oxidation of its cysteine residues [20]. Recently, loss of PTEN expression has been reported in a high percentage of human sarcomatoid MPM as compared with other subtypes [15].…”
Section: Discussionmentioning
confidence: 99%
“…As a class I carcinogenic heavy metal, arsenic can increase ROS levels via Fenton reaction, thus participating in the progressions of multiple malignancies 13 , 14 . Inhaled asbestos fibers accumulate in lungs and induce the generation of ROS due to the presence of iron associated with the fibrous silicates, which promote the malignant transformation of mesothelial cells 15 . Ultraviolet radiation (UVR) increases oxidative stress not only by upregulating nitric oxide synthase (NOS) synthesis but also by impeding catalase (CAT) to scavenge hydrogen peroxide, thus leading to increased risk of sunburn, photoaging and skin cancer 16 .…”
Section: Sources Of Rosmentioning
confidence: 99%
“…The PI3K/Akt signaling pathway is involved in cell survival and its activity can be redox-regulated. This point is particularly relevant in MPM, since it is well known that asbestos toxicity is mainly related to the release of ROS [ 74 , 75 ]. The analysis of transcriptomes and whole exomes confirmed that the PI3K/mTor pathways are activated in MPM [ 76 ].…”
Section: Germline and Somatic Changesmentioning
confidence: 99%